2023
DOI: 10.1590/0103-8478cr20220543
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nutritional stress in sugarcane by VIS-NIR-SWIR reflectance spectroscopy

Abstract: This study applied spectroradiometry techniques with hyperspectral data to identify the correlations between sugarcane leaf reflectance and the contents of Nitrogen (N), phosphorus (P), Potassium (K), Sulfur (S), Calcium (Ca) and Magnesium (Mg). During the harvests 2019/20 and 2020/21, sugarcane was introduced to nutritional stress by the application of limestone doses. Liming was applied in a fractional way and, at the end of five years, the amounts corresponded to 0, 9, 15 and 21 t ha-1 of dolomitic limeston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, it is already used to evaluate the nitrogen status (N) in cultures such as rice [ 11 ]; tea leaves [ 9 ]; cotton [ 12 ]; apple [ 13 ]; soybean, tepary bean and mothbean [ 14 ] and spinach [ 15 ]. In general, these studies have shown good performance of Vis-NIR-SWIR spectroradiometry in estimating parameters related to agricultural crops, since N is closely related to the visible (400–700 nm) and red-edge (670–780 nm) bands [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is already used to evaluate the nitrogen status (N) in cultures such as rice [ 11 ]; tea leaves [ 9 ]; cotton [ 12 ]; apple [ 13 ]; soybean, tepary bean and mothbean [ 14 ] and spinach [ 15 ]. In general, these studies have shown good performance of Vis-NIR-SWIR spectroradiometry in estimating parameters related to agricultural crops, since N is closely related to the visible (400–700 nm) and red-edge (670–780 nm) bands [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Differently from other crops, there are few studies considering the use of spectroradiometry for the evaluation of leaf contents in sugarcane, and they are even more scarce for the Brazilian conditions [ 16 , 20 ]. Conversely, the existing works indicate a great potential of the technique [ 16 , 17 , 21 ]. Despite presenting promising perspectives, most of these studies have directed their efforts to the quantification of the N content in only one vegetative stage of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limitations in quantifying the elements with atomic numbers (Z) higher than 12 and the need to consider radiation effects during analysis necessitate the careful evaluation of these methods. Also, Vis-NIR has been used to quantify the nutrients [15,16].…”
Section: Introductionmentioning
confidence: 99%